(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
The youngest tephra deposits of Seminung Volcano in South Sumatra, Indonesia, was studied by addressing the stratigraphy (field data), componentry, petrography, glass and mineral compositions, and textural analysis of vesicles to interpret the magmatic system and eruption dynamics. Based on the componentry and grain size characteristics, the section is divided into three different units: (1) massive block and ash, (2) interbedded ash and lapilli, and (3) massive lapilli. All units include grey pumice (GP), brown pumice (BP), and scoria (SC) as the main juvenile types, while porphyritic lava occurs as the non-juvenile phase (lithics). Noteworthy, minor banded pumice (BaP) can be observed in all units, and accretionary lapilli (AL) is exclusive in the interbedded ash and lapilli unit. The similarity in mineralogy and the linear correlation of all major elements of glass compositions suggest that grey and brown pumice originated from the same shallow, biotite-bearing more silicic magma (64.5-74.9 wt. % ), while scoria originates from the deeper, biotite-free less silicic magma (62.1-69.2 wt. % ). The fact that grey pumice shows higher silica content and pheno-bubble fraction with lower phenocryst content than brown pumice suggests the rough stratification of the more silicic magma reservoir. Furthermore, the more silicic magma was likely intruded by the deeper less silicic magma, as indicated by the bimodal distribution of anorthite (An#) in grey and brown pumices (i.e. the peak of the high anorthite content is similar to that of scoria). Thus, the accumulation of pheno-bubble and magmatic recharge were likely responsible for triggering the eruption. Finally, the fact that juvenile clasts from units 2 and 3 had the highest matrix-vesicle number density (MVND) implies that the eruption intensity reached its peak towards the final eruption stage.